Human resources role in redefining the workplace diversity - Oswal, Nidhi (Opción, 2019)
The study aims to investigate the role of human resources in redefining workplace diversity via comparative qualitative research methods. As a result, a secure and known environment helps neurodivergent people to exhibit their skills to their maximum. In conclusion, Programs like „Autism at work‟ and „Neurodiversity hub‟ should be more accelerated and furthermore, platforms should be open for the neurodivergent population to be part of a diverse workforce